ANALYSIS OF OXYGEN CONCENTRATION VALUES IN PORTABLE OXYGEN CONCENTRATOR DEVICES BY USING SILICA GEL AS FILTRATION MATERIAL - Syahrul Ramadhan Ardiansyah; Akbar Sujiwa (BEST, 2023)
Oxygen concentrators as a means of separating pure oxygen from free air became an item that was quite sought after when the pandemic case hit in the past 2020 to 2021. This device works by taking free air around us and then processing it by passing the air through a filter so that oxygen is separated from other gases, most of which are nitrogen. However, not all oxygen generator devices are able to filter oxygen to the maximum, this depends on the filtration material used. Most portable oxygen generator devices use synthetic zeolite as a filtration material, but have not maximally filtered oxygen, therefore in this study researchers examined the effect of using silica gel when used as an oxygen filtration medium in the same oxygen concentrator device. In the results of this study, it was found that there was an increase in the oxygen concentration from the standard media device using synthetic zeolite compared to using silica gel material, the increase in oxygen concentration that occurred increased by around 3.3%.